Current and ideal practice of quality management in Malaysia / Julian Paul Sidin … [et al.] - Sidin, Julian Paul; Wafa, Syed Azi; Felix, Jules; G.V, Sherry (University Publication Centre (UPENA), 2007)
Theory building efforts in total quality management have begun in earnest. However, there is now such a diversity of things done under the name of total quality management that it has become unclear whether TQM still has an identifiable conceptual core. The study addresses several questions, including: (I) How do managers describe its quality environment? (2) How do managers perceive what quality management should be practiced? (3) What are the current practices of quality management now being practiced by them? (4) What is the relationship between organizational quality context and the current and ideal quality management?